DISCOURSE-ANALYSIS AS A METHOD OF ANALYSIS OF SOCIAL TRANSFORMATIONS - Mukhina, O. M. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2017)
The article actualizes the potential of discourse analysis as a way of studying the social field, social metamorphosis and the process of space production. In this connection, the socio-philosophical theories of the followers of historical materialism on the one hand, and the poststructuralist discourse theory on the other, are considered. The dialectic correlation of discursive and material social practices is investigated. Based on the results obtained, it is concluded that discourse analysis has a great heuristic potential as one of the social-critical methods.